2021
DOI: 10.1093/jxb/erab327
|View full text |Cite
|
Sign up to set email alerts
|

Improving C4 photosynthesis to increase productivity under optimal and suboptimal conditions

Abstract: Although improving photosynthetic efficiency is widely recognised as an underutilized strategy to increase crop yields, research in this area is strongly biased towards species with C3 photosynthesis relative to C4 species. Here, we outline potential strategies for improving C4 photosynthesis to increase yields in crops by reviewing the major bottlenecks limiting the C4 NADP-ME pathway under optimal and suboptimal conditions. Recent experimental results demonstrate that steady state C4 photosynthesis under non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 202 publications
2
31
0
Order By: Relevance
“…Rubisco has been speculated to be especially limiting in chilling conditions in C 4 species, since C 4 plants contain less Rubisco and because Rubisco is operating closer to its maximum capacity due to the high concentration of CO 2 created by the carbon-concentrating mechanism ( Sage and McKown, 2006 ). Furthermore, enhanced degradation of photosynthetic gene products under chilling stress reduces the amounts of enzymes in the leaf: protein breakdown is increased at low temperatures (reviewed by Sales et al , 2021 ). Specifically, the photosynthetic enzymes pyruvate, phosphate dikinase (PPDK; BRENDA: EC 2.7.9.1), PEPC, and Rubisco break down more easily under chilling conditions in C 4 species ( Kingston-Smith et al , 1997 ; Du et al , 1999 ; Chinthapalli et al , 2003 ).…”
Section: Physiology Of Photosynthetic Chilling Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Rubisco has been speculated to be especially limiting in chilling conditions in C 4 species, since C 4 plants contain less Rubisco and because Rubisco is operating closer to its maximum capacity due to the high concentration of CO 2 created by the carbon-concentrating mechanism ( Sage and McKown, 2006 ). Furthermore, enhanced degradation of photosynthetic gene products under chilling stress reduces the amounts of enzymes in the leaf: protein breakdown is increased at low temperatures (reviewed by Sales et al , 2021 ). Specifically, the photosynthetic enzymes pyruvate, phosphate dikinase (PPDK; BRENDA: EC 2.7.9.1), PEPC, and Rubisco break down more easily under chilling conditions in C 4 species ( Kingston-Smith et al , 1997 ; Du et al , 1999 ; Chinthapalli et al , 2003 ).…”
Section: Physiology Of Photosynthetic Chilling Tolerancementioning
confidence: 99%
“…While this review focuses on pre-existing variation in chilling tolerance of photosynthesis in maize, and the genomic regions related to this tolerance which may be utilized in breeding programmes, it is worth noting that genetic modification approaches also offer valuable tools for improving photosynthesis and chilling tolerance. For example, increasing Rubisco and electron transport capacity can improve the photosynthetic performance of C 4 plants; Rubisco is predicted to have a greater effect on chilling recovery than other photosynthetic enzymes in the C 4 pathway ( Sales et al , 2021 ). The overexpression of Rubisco large and small subunits, in concert with Rubisco Assembly Factor 1 (RAF1), increased maize Rubisco content by >30% (although Rubisco activase is probably a vital factor for translating this increased enzyme content into a proportional increase in photosynthetic activity); this overexpression of Rubisco can speed recovery following chilling stress ( Salesse-Smith et al , 2018 ).…”
Section: High-throughput Breeding Approachesmentioning
confidence: 99%
“…This review focuses on the photosynthetic light‐dependent reactions, the optimization of which is relevant to improving both C3 and C4 photosynthesis in plants and photosynthetic micro‐organisms (Leister, 2012; Ruban, 2015; von Caemmerer and Furbank, 2016; Cardona et al, 2018; Simkin et al, 2019; Batista‐Silva et al, 2020; Ermakova et al, 2021b; Sales et al, 2021; Santos‐Merino et al, 2021). Modeling studies have suggested that improving the quantum yield and electron transport capacity have a greater potential for increasing the productivity of crops than other photosynthetic mechanisms, such as improving Rubisco activity (Gu et al, 2014; Yin and Struik, 2015, 2021a; Wu et al, 2019).…”
Section: Introduction—why Do We Need Crops With Increased Yields?mentioning
confidence: 99%
“…However, previous studies have documented the potential benefit of improving crop performance by selecting for enhanced J max , which has been correlated with increased final biomass as well as increased levels of CO 2 assimilation (Gu et al, 2014; Sales et al, 2021). While it may be difficult to understand the role of source‐limitation in elevated [CO 2 ] within the context of this study, especially since the plants that were utilized were not acclimated to elevated [CO2], there is still much promise and merit in the selection of traits such as J max and V cmax as a method to improve overall photosynthetic performance.…”
Section: Responsementioning
confidence: 99%